Corporate Governance and Credit Rating in MENA Region - Nouira, Amirah; Omri, Mohamed Ali Brahim (International Journal of Economics, Management and Accounting, 2025)
This study attempts to detect the impact of governance mechanisms on the credit rating of MENA region companies. This research uses the Logit model. It is most widely used in failure early warning models. Using a sample of 23 firms in the MENA region rated by the rating agency "Fitch Ratings" during the period 2010-2020, this study found that increasing board size and ownership concentration have positive effects on firm credit rating, while increasing duality, institutional ownership, and managerial ownership have a negative effect. These results offer valuable insights for companies looking to enhance their governance systems and make informed investments in favorable conditions. The findings have significant implications for investors, since incorporating governance mechanisms into the rating process can assist companies in enhancing ratings. Indeed, rating agencies assess corporate governance by focusing on four key elements: ownership structure and influence, rights and relationships with financial stakeholders, financial transparency, and the structure and process of the board of directors. They strongly believe that rating agencies evaluate corporate governance based on four primary factors: ownership structure and influence, rights and relationships with financial stakeholders, transparency and financial structure, as well as the board's procedures. It is their belief that inadequate corporate governance can compromise a company's ability to meet its debt obligations and increase potential losses for its creditors. As capital markets are an important source of financing for emerging markets, the importance of credit rating agencies in providing standardized credit risk assessments for emerging market investments has continued to grow.